Operation And Control Strategies Of Integrated Distributed Energy Resources : A Review - A.Rahman, Hasimah; Majid, Md.Shah; Jordehi, A.Rezaee; Gan, Chin Kim; Hassan, Mohammad Yusri; O.Fadh, Saeed (Elsevier, 2015)
-